Development and preliminary data on the use of a mobile app specifically designed to increase community awareness of invasive pneumococcal disease and its prevention. Issue 4 (2nd April 2016) - Panatto, Donatella; Domnich, Alexander; Gasparini, Roberto; Bonanni, Paolo; Icardi, Giancarlo; Amicizia, Daniela; Arata, Lucia; Bragazzi, Nicola Luigi; Signori, Alessio; Landa, Paolo; Bechini, Angela; Boccalini, Sara
ABSTRACT: Given the growing use and great potential of mobile apps, this project aimed to develop and implement a user-friendly app to increase laypeople's knowledge and awareness of invasive pneumococcal disease (IPD). Despite the heavy burden of IPD, the documented low awareness of IPD among both laypeople and healthcare professionals and far from optimal pneumococcal vaccination coverage, no app specifically targeting IPD has been developed so far. The app was designed to be maximally functional and conceived in accordance with user-centered design. Its content, layout and usability were discussed and formally tested during several workshops that involved the principal stakeholders, including experts in IPD and information technology and potential end-users. Following several workshops, it was decided that, in order to make the app more interactive, its core should be a personal "checker" of the risk of contracting IPD and a user-friendly risk-communication strategy. The checker was populated with risk factors identified through both Italian and international official guidelines. Formal evaluation of the app revealed its good readability and usability properties. A sister web site with the same content was created to achieve higher population exposure. Seven months after being launched in a price- and registration-free modality, the app, named " Pneumo Rischio, " averaged 20.9 new users/day and 1.3 sessions/user. The first in-field results suggest that " Pneumo Rischio " is a promising tool for increasing the population's awareness of IPD and its prevention through a user-friendly risk checker.